Искупление: роман / Олег Рой - Рой Олег Юрьевич (Цветочная коллекция, 2022)
Экземпляры: (20230703) / Инвентарный номер: 42544 / Цена: 383.00 / Сис.шифр: 84(2=411.2)6 / Авт.знак: Р 65 / ГРНТИ: 17 / ББК: 84(2=411.2)6-446